Comparison of cattle types and management systems - R.R. Schalles; K. Bolsen; Michael E. Dikeman (Kansas Agricultural Experiment Station Research Reports, 1983)
No differences were found in total feed energy required to produce a pound of retail cuts between breeds or management systems. However, across breeds, faster gaining steers were more efficient. When yardage, facilities, labor and interest were also considered, faster gaining cattle and accelerated management programs were more economical.
Keywords: Cattlemen' s Day; 1983; Report of progress (Kansas State University. Agricultural Experiment Station); 427; Beef; Gain; Management programs